Ferroelectric PZT thin films for photovoltaic application. (January 2020) - Gupta, Reema; Gupta, Vinay; Tomar, Monika
Abstract: The ferroelectric photovoltaic response characteristics of Lead Zirconate Titanate (PZT) thin film in metal-ferroelectric-metal (MFM) configuration is studied under 33 mode upon exposure to UV radiations. PZT thin films of 180 nm are prepared on inter-digital electrodes patterned silicon substrate (with silicon dioxide as insulating layer) using chemical solution deposition (CSD) technique followed by rapid thermal annealing. PZT thin films are found to be in single phase and possess high electrical polarization (50μC/cm 2 ). Significant increase in photocurrent and large value of open circuit voltage (1.0 V) is observed for the prepared ferroelectric photovoltaic film under UV illumination.